Review of literature on decision support systems for natural hazard risk reduction: Current status and future research directions. (October 2017) - Newman, Jeffrey Peter; Maier, Holger Robert; Riddell, Graeme Angus; Zecchin, Aaron Carlo; Daniell, James Edward; Schaefer, Andreas Maximilian; van Delden, Hedwig; Khazai, Bijan; O'Flaherty, Michael John; Newland, Charles Peter
Abstract: Natural hazard risk is largely projected to increase in the future, placing growing responsibility on decision makers to proactively reduce risk. Consequently, decision support systems (DSSs) for natural hazard risk reduction (NHRR) are becoming increasingly important. In order to provide directions for future research in this growing area, a comprehensive classification system for the review of NHRR-DSSs is introduced, including scoping, problem formulation, the analysis framework, user and organisational interaction with the system, user engagement, monitoring and evaluation. A review of 101 papers based on this classification system indicates that most effort has been placed on identifying areas of risk and assessing economic consequences resulting from direct losses. However, less effort has been placed on testing risk-reduction options and considering future changes to risk. Furthermore, there was limited evidence within the reviewed papers on the success of DSSs in practice and whether stakeholders participated in DSS development and use. Highlights: Classification system of different aspects of natural hazard risk-reduction DSSs. Aspects covered are scoping, analysis, user interaction, monitoring and evaluation. Review of 101 papers detailing 77 DSSs using proposed classification system. Good coverage of hydrological hazards, structural mitigation and economic impact. Limited coverage of multiple hazards, future impacts and DSS use and evaluation.